High-precision refraction correction of ICESat-2 bathymetry based on sea-wave profiles with a piece-point polynomial model - Chen, Yifu; Zhao, Qian; Le, Yuan; Wu, Lin; Song, Wuxing; Zhou, Liqin; Wang, Lizhe (Frontiers in Marine Science, 2025)
The Ice, Cloud, and Land Elevation Satellite-2 (ICESat-2), featuring the advanced topographic laser altimeter system (ATLAS), pioneered spaceborne photon-counting LiDAR technology. The first spaceborne laser system in Earth’s orbit with water detection capabilities, offers a more direct approach for charting the bathymetry and underwater topography in coastal waters. However, the refraction effect of water column on light is not taken into account by ATLAS products, which will cause the position change of signal photons on the seafloor, consequently reducing the precision of nearshore bathymetry and underwater topography mapping. In the previous studies, the fluctuation water surface has been assumed as the plane to achieve the water refraction correction. In this process, the water incident angle, refraction angle and water refraction direction are same for all seafloor photons, which decreases the accuracy of the photon position and the nearshore bathymetry. Therefore, we present an innovative method for addressing refraction correction by tracking the trajectory of individual photons on the seafloor and reconstructing sea-wave profiles to achieve high-accuracy refraction correction for ATLAS data. In this method, the instantaneous sea wave has been modeled using the extracted signal photon of water surface and the proposed weight cubic polynomial model. Further, the corresponding various incident and refraction angles of each seafloor photon were accurately obtained to calculate various the displacement quantity and direction. Moreover, a coordinate correction model was introduced to aim at enhancing the accuracy of photon coordinates on the seafloor and mapping of underwater topography. Validation results demonstrate that the proposed method for refraction correction effectively enhances the bathymetric precision. The maximum depth displacement corrected in the study area reached 5.46 m, occurring at a water depth of 16.01 m. In the along-track direction, there was a range of maximum displacements from -0.54 to 0.47 m, while the maximum relative displacement reached 1.01 m, significantly exceeding the displacement observed in the cross-track direction.